1987
DOI: 10.1123/ssj.4.1.48
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Children’s Legitimacy Judgments and Their Moral Reasoning, Aggression Tendencies, and Sport Involvement

Abstract: The purpose of this study was to investigate (a) the relationship between children’s judgments regarding the legitimacy of potentially injurious sport acts for adults and for children, (b) the relationships between children’s legitimacy judgments and their moral reasoning, aggression tendencies, and sport involvement, and (c) the relative ability of the latter three variables to predict legitimacy judgments. Analyses were based on 78 girls and boys in grades 4 through 7 who participated in a moral interview, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0
7

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 13 publications
5
51
0
7
Order By: Relevance
“…Bredemeier et al (1986) found that the extent of boys' involvement in high contact sports such as football, wrestling, and judo, and girls' involvement in medium contact sports such as soccer and basketball, was associated with less mature moral reasoning and greater selfreported tendencies to be aggressive in both sport and daily life. These findings were corroborated by two other studies, which revealed that extensive participation in medium contact sport among young people (Conroy, Silva, Newcomer, Walker, & Johnson, 2001), and in high contact sports among boys at a summer camp (Bredemeier et al, 1987), corresponded to judgments that aggressive behaviors in sport are legitimate. Interestingly, participation in noncontact sports such as gymnastics, golf, swimming, and track and field did not emerge as a predictor of any dimension of morality in these studies.…”
supporting
confidence: 80%
See 4 more Smart Citations
“…Bredemeier et al (1986) found that the extent of boys' involvement in high contact sports such as football, wrestling, and judo, and girls' involvement in medium contact sports such as soccer and basketball, was associated with less mature moral reasoning and greater selfreported tendencies to be aggressive in both sport and daily life. These findings were corroborated by two other studies, which revealed that extensive participation in medium contact sport among young people (Conroy, Silva, Newcomer, Walker, & Johnson, 2001), and in high contact sports among boys at a summer camp (Bredemeier et al, 1987), corresponded to judgments that aggressive behaviors in sport are legitimate. Interestingly, participation in noncontact sports such as gymnastics, golf, swimming, and track and field did not emerge as a predictor of any dimension of morality in these studies.…”
supporting
confidence: 80%
“…A number of studies (Bredemeier & Shields, 1986a;Bredemeier et al, 1986Bredemeier et al, , 1987Conroy et al, 2001;Silva, 1983) have revealed that athletes who have participated extensively in medium or high contact sports display aggressive tendencies, judgments that injurious acts are legitimate, or low levels of moral reasoning. Such relationships, however, have not been identified in athletes of noncontact sports such as swimming, gymnastics, or golf (Bredemeier & Shields, 1986b;Bredemeier et al, 1986;Conroy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations